Engineering an egg-shell structure for the Ag/SiO2 pellet catalyst for selective hydrogenation of dimethyl oxalate to methyl glycolate. (14th March 2023) - Xu, Xiaofeng; Hu, Xin; Luo, Zuwei; Cao, Yueqiang; Zhu, Yi-An; Li, Wei; Zhou, Jinghong; Zhou, Xinggui
Abstract : An egg-shell-type Ag/SiO2 pellet catalyst with an optimized thickness of the Ag-shell exhibits both enhanced activity and selectivity for DMO hydrogenation to MG. Abstract : Egg-shell-type Ag/SiO2 pellet catalysts with various Ag-shell thicknesses, in which the structures of Ag active sites are similar, are controllably synthesized for exploring the diffusion effects on DMO hydrogenation to MG. The egg-shell-type pellet catalyst with an optimized thickness of the Ag-shell exhibits enhanced hydrogenation activity and MG selectivity.